2021
DOI: 10.1590/0004-282x20200105
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrocardiogram during routine electroencephalogram: arrhythmia rates through the eyes of the cardiologist

Abstract: Background: The importance of simultaneous 2-lead electrocardiogram (ECG) recording during routine electroencephalogram (EEG) has been reported several times on clinical grounds. Objective: To investigate arrhythmia rates detected by simultaneous 2-lead ECG in our patient sample undergoing routine EEG. Remarkably, we sought to assess the possible expansion of results with a more experienced interpretation of simultaneous ECG. Methods: Simultaneous 2-lead ECG recordings during routine EEG, performed between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 32 publications
2
7
3
Order By: Relevance
“…Our findings indicated that arrhythmias in total were more common in older patients, similar to Onder et al [20] but contrary to Kendirlie et al [3]. The differences are likely due to the different studied populations and different subtypes of reported arrhythmias.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our findings indicated that arrhythmias in total were more common in older patients, similar to Onder et al [20] but contrary to Kendirlie et al [3]. The differences are likely due to the different studied populations and different subtypes of reported arrhythmias.…”
Section: Discussionsupporting
confidence: 52%
“…Kendirli et al retrospectively detected EKG abnormalities in 18% of 376 patients who had a minimum of 20 min artifact-free EEG, the most common of which was supraventricular tachycardia [3]. Another study conducted by Onder et al in which simultaneous EKGs during 478 routine EEGs performed over three months were retrospectively scanned by a cardiologist and found that 80 (17%) patients had arrhythmias with ventricular extrasystole being the most frequent one [20]. The higher frequency of EKG abnormalities in our study could be attributed to the difference in patients' demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kendirli et al 8 detected ECG abnormalities in 68 (18%) of 376 patients (16–83 years of age) who underwent EEG testing due to prediagnosis of epilepsy or convulsive syncope. Onder et al 10 reported that the rate of arrhythmia was 17% on simultaneous ECG-EEG recordings by a cardiologist's evaluation in 478 adult patients who underwent routine testing. Yassin et al 11 evaluated 433 recordings of 365 adult patients (mean age: 46.8 years) and found ECG abnormalities in 28.5% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 The extended ECG trace which accompanies the EEG can also provide more insights into potential cardiac causes of presentations. 4,[7][8][9] The diagnostic utility of a concurrent ECG is relatively unknown. Previous studies have commented on its particular usefulness in syncope and the detection of newly identified cardiac dysrhythmias.…”
Section: Introductionmentioning
confidence: 99%